2012
DOI: 10.3109/15412555.2011.650802
|View full text |Cite
|
Sign up to set email alerts
|

Components of the COPD Assessment Test (CAT) associated with a diagnosis of COPD in a random population sample

Abstract: The aim of this study was to determine if components of the COPD Assessment Test (CAT), a validated health status impairment instrument, had additional utility in identifying patients at risk for COPD in whom spirometry testing is appropriate. This study was part of the Canadian Obstructive Lung Disease prevalence study. Consenting participants ≥ 40 years of age were identified by random digit dialing. Smoking history, 8-item CAT scores, and post-bronchodilator spirometry were recorded for each. Stepwise logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 32 publications
6
54
2
Order By: Relevance
“…9 It is lower than rates of 9%-10% expected based on population-based studies using physiologic measures. 2,6,22 This difference is consistent with past studies that found COPD to be underdiagnosed or misdiagnosed quite frequently. Frank and colleagues 23 found that less than half of patients with Global Obstructive Lung Disease categories 2-4 by spirometry had a diagnosis of COPD recorded in their primary care medical records.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…9 It is lower than rates of 9%-10% expected based on population-based studies using physiologic measures. 2,6,22 This difference is consistent with past studies that found COPD to be underdiagnosed or misdiagnosed quite frequently. Frank and colleagues 23 found that less than half of patients with Global Obstructive Lung Disease categories 2-4 by spirometry had a diagnosis of COPD recorded in their primary care medical records.…”
Section: Discussionsupporting
confidence: 82%
“…6 There are limited data on COPD either alone or in combination with other chronic diseases from primary care settings.…”
Section: Cmaj Open 3(1) E15mentioning
confidence: 99%
“…15,21 Other questionnaires such as the COPD Population Screener Questionnaire (COPD-PS) and a condensed version of the COPD Assessment Test (CAT) have been developed but have not undergone external validation. 13,14 The aim of this study was to validate the CDQ externally in a large sample of current and former smokers with no prior diagnosis of obstructive lung disease recruited from general practices in Sydney, Australia. We wanted to determine if the CDQ could be used as a COPD diagnostic tool in patients at increased risk in Australian general practice.…”
mentioning
confidence: 99%
“…5 Several studies in different populations around the world have looked at devising a questionnaire for the diagnosis of COPD or, alternatively, using a questionnaire as a filter to select people at risk (such as tobacco smokers, passive tobacco exposure, and increasing age) for further investigation by spirometry. [9][10][11][12][13][14] The COPD Diagnostic Questionnaire (CDQ) is an eight-item tool designed by the COPD Questionnaire Study Group from a cross-sectional study of primary care patients aged >40 years from the UK and USA with a history of smoking but no prior respiratory diagnosis (see Appendix 1, available online at www.thepcrj.org). 11,12 It was developed to improve the efficiency and accuracy of COPD diagnosis in primary care by removing the need for spirometry in low-risk patients.…”
mentioning
confidence: 99%
“…The American Thoracic Society (ATS) and the European Respiratory Society (ERS) defines pulmonary rehabilitation as "a comprehensive intervention based on a thorough patient assessment followed by patient-tailored therapies that include, but are not limited to, exercise training, education, and behaviour change, designed to improve the physical and psychological condition of people with chronic respiratory disease and to promote the long-term adherence to health-enhancing behaviours" and states that it is the best available means to improve health status in patients with COPD who are symptomatic despite otherwise optimal therapy at the start of a pulmonary rehabilitation program (68). Indeed, previous research shows psychosocial, physiological, symptom-reducing and health economic benefits after pulmonary rehabilitation in patients with COPD (69).…”
Section: Treatmentmentioning
confidence: 99%